Rotator cuff tears: pathology and non-surgical management - Aboelmagd, T; Rees, J; Gwilym, S (Elsevier, 2018)
Rotator cuff tears may be caused by intrinsic (biochemical) or extrinsic (physical) mechanisms, or a combination. They may also be classified as traumatic (acute) or non-traumatic (sub-acute). Due to an on-going lack of literature on natural history and disease progression, a variety of treatment approaches to manage these tears exists and consequently consensus views can fluctuate. This article will focus on the anatomy of the rotator cuff and the pathology that may affect it, before discussing the non-operative approaches commonly used. A potential algorithm for management is proposed, highlighting the timings to consider for surgical intervention.